2023
DOI: 10.1021/acsomega.2c08048
|View full text |Cite
|
Sign up to set email alerts
|

Serum Lipidomic Analysis Reveals Biomarkers and Metabolic Pathways of Thyroid Dysfunction

Abstract: Abnormal thyroid hormone secretion is the most important feature of hypothyroidism and plays an important role in lipid metabolism. However, their connection has not been clearly established. This study aimed to identify the serum biomarkers and metabolic pathways associated with hyperthyroidism and hypothyroidism. The study enrolled discovery and validation sets of 175 and 300 participants, respectively, to identify and validate the serum biomarkers of hyperthyroidism and hypothyroidism via ultrahigh performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 41 publications
2
5
0
Order By: Relevance
“…The data are consistent with the results of pathway analysis (see Section 2.3 ) as they show details regarding specific variations of different classes of metabolites, identifying either common metabolic signatures of PTC and BT or specific alterations for each pathology group, compared to controls. These findings are consistent with other previous experimental data obtained by LC–MS or NMR analysis of serum PTC and/or BT (hypo- and hyperthyroidism) samples that also confirmed the presence of specific alterations of these metabolic pathways [ 24 , 25 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The data are consistent with the results of pathway analysis (see Section 2.3 ) as they show details regarding specific variations of different classes of metabolites, identifying either common metabolic signatures of PTC and BT or specific alterations for each pathology group, compared to controls. These findings are consistent with other previous experimental data obtained by LC–MS or NMR analysis of serum PTC and/or BT (hypo- and hyperthyroidism) samples that also confirmed the presence of specific alterations of these metabolic pathways [ 24 , 25 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ].…”
Section: Resultssupporting
confidence: 93%
“…In addition, increased levels of bile acids were correlated with the upregulated FFA metabolism, which was observed in the BT group. These data are confirmed by the findings of different study groups [ 24 , 25 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ], their results being related to the same categories of metabolites.…”
Section: Discussionsupporting
confidence: 76%
“…Serum lipidomic analyses have also been performed to help identify the serum biomarkers and metabolic pathways associated with hypothyroidism. A recent study enrolled 175 individuals for a discovery set and 300 for a validation set (TSH values 23–27 mIU/L) [ 43 ]. Using this approach 6 potential biomarkers were identified for hypothyroidism which were involved in glycerophospholipid metabolism.…”
Section: Metabolomics Lipidomicsmentioning
confidence: 99%
“…Using this approach 6 potential biomarkers were identified for hypothyroidism which were involved in glycerophospholipid metabolism. A biomarker panel using the six hypothyroidism biomarkers showed good ability to distinguish patients with hypothyroidism from the healthy population with an area under the curve of 0.97, sensitivity of 86%, and specificity of 96% [ 43 ]. Similar approaches have been taken using proteomics and metabolomics to identify a combination of proteins and metabolites that can distinguish hypothyroidism from the euthyroid state [ 44 ].…”
Section: Metabolomics Lipidomicsmentioning
confidence: 99%
“…For instance, Jaber et al and Lee et al demonstrated serum metabolic profile alterations after ATD treatment in newly diagnosed hyperthyroid patients [ 16 , 17 ]. In addition, Dong et al analyzed hyperthyroidism, hypothyroidism, and healthy subjects and discovered a novel lipid-metabolism marker regulated by TH that was involved in human metabolism [ 18 ]. Jiang et al evaluated the differential proteomics of tears in patients with Grave’s orbitopathy and healthy subjects [ 19 ].…”
Section: Introductionmentioning
confidence: 99%